Molecular identification and functional analysis of the putative ecdysone receptor in Spodoptera litura - Tong, Ziqian; Shi, Huixuan; Liu, Zhuo; Zhang, Donghai; Li, Dandan; Kan, Yunchao; Qiao, Huili (Journal of Asia-Pacific entomology, 2025)
[Display omitted] •The putative ecdysone receptor isoform A (SlEcRA) was characterized in Spodoptera litura.•SlEcRs was regulated by 20E and involved in the larval development of S. litura.•Knockdown of SlEcRs inhibited larval growth and increased larval mortality.•Chitosan/dsRNA nanoparticles significantly improved the RNAi efficiency and larvae mortality.•Silencing of SlEcRs increased larval susceptibility to insecticide, emamectin benzoate. 20-hydroxyedysone (20E) is an important hormone that regulates the process of molting and metamorphosis in insects. Ecdysone receptor (EcR) is one of the most important primary nuclear receptor for 20E. To clarify the essential function of EcR during the development of Spodoptera litura, the gene encoding the putative ecdysone receptor isoform A (SlEcRA) was cloned and verified. Multiple sequence comparisons and the subsequent phylogenetic study indicated that SlEcRA protein exhibited a high degree of conservation and significant homology with EcRA proteins in other insects. Spatiotemporal expression analysis showed that SlEcRs were predominantly expressed during the larval molting and prepupa stages, with the highest expression in fat body. Moreover, the expression of SlEcRs were induced by 20E in fat body, midgut and integument. Silencing of SlEcRs led to increased mortality and decreased larval weight during larval development. A combination treatment of dsSlEcRs and low-concentration emamectin benzoate effectively increased larvae mortality at 48 h. Furthermore, the larval mortality of Chi-dsSlEcRs nanoparticles by epidermal infiltration was much higher than the naked dsSlEcRs by injection. Co-delivery of Chi-dsSlEcRs and emamectin benzoate exhibited shorter action time and higher mortality rate on larvae. These findings not only highlight the potential of the putative SlEcR as an RNA interference target for S. litura control, but also provide a new idea for reducing the reliance on chemical insecticides in agricultural pest control.